2016
DOI: 10.1149/2.1121614jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Bright Nickel from Liquid Ammonia Solution Containing Chloride

Abstract: The present work aims to prepare bright nickel from liquid ammonia solution containing chloride. The effect of sodium benzenesulfinate concentration on the current efficiency, electrochemical nucleation behavior, crystallographic orientations and surface morphology at macro and micro level of the electrodeposited nickel were studied systematically. Results show that the introduction of sodium benzenesulfinate can efficiently transfer the black nickel to smooth, compact and dense nickel. X-ray diffraction revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The great enhancement of the anodic peaks may have resulted from the fast oxidation of nickel deposits and the change in the crystal structure induced by TU. This phenomenon was also observed by Wu,4 who studied the effect of sodium benzenesulfinate on nickel electrodeposition from a liquid ammonia solution containing chloride. The potential difference between the nucleation potential (E nu ) and cross overpotential (E co ) is the nucleation overpotential (NOP), which can be regarded as an indicator of the extent of cathodic polarization.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The great enhancement of the anodic peaks may have resulted from the fast oxidation of nickel deposits and the change in the crystal structure induced by TU. This phenomenon was also observed by Wu,4 who studied the effect of sodium benzenesulfinate on nickel electrodeposition from a liquid ammonia solution containing chloride. The potential difference between the nucleation potential (E nu ) and cross overpotential (E co ) is the nucleation overpotential (NOP), which can be regarded as an indicator of the extent of cathodic polarization.…”
Section: Resultssupporting
confidence: 72%
“…For instance, Wu et al introduced sodium benzenesulfinate (SBS) to an ammoniacal solution and found that SBS efficiently improved the formation of smooth and dense nickel. 4 Lu found that dodecyl sodium sulfate (SDS) can act as a wetting agent to decrease cathode polarization and eliminate the pitting of nickel deposits from sulfate systems. 5 The use of additives in electrodeposition is extremely important, due to the special roles that additives play in metal deposition.…”
mentioning
confidence: 99%
“…Nickel and its alloys, with the merits of low-cost, accessibility, and excellent catalytic activity, are deemed as alternative candidates for precious metal catalysts. [1,[9][10][11][12][13][14][15][16][17] Compared with the known Ni-Mo alloys, Ni-P alloys outperform because the negatively charged P not only easily captures the positively charged protons to activate the HER but also improves the corrosion resistance of the electrode. [18][19][20][21] As is widely accepted, Ni-P alloys are commonly fabricated by electroless plating, where the bath solution is based on the use of the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…NiCl 2 and NH 4 Cl are important and familiar compositions in chloride hydrometallurgy for nickel and other valuable metals. Wu studied the electrodeposition of bright nickel from ammonia solution with chloride and disclosed the deposition behaviors of nickel with the change of solution concentration . Therefore, the NiCl 2 –NH 4 Cl–H 2 O system is important in hydrometallurgy and need to be further studied.…”
Section: Introductionmentioning
confidence: 99%